The effects of psychostimulants on cognitive functions in individuals with attention-deficit hyperactivity disorder: A systematic review. (May 2022) - Mckenzie, Andrea; Meshkat, Shakila; Lui, Leanna M.W.; Ho, Roger; Di Vincenzo, Joshua D.; Ceban, Felicia; Cao, Bing; McIntyre, Roger S.
Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) is associated with a broad range of deficits in cognitive functions which has significant implications for quality of life. Psychostimulants are demonstrated to improve symptoms of inattention and hyperactivity/impulsivity, however, their impact on cognition remains incompletely characterized. Herein, the aim of this systematic review is to synthesize the extant literature reporting on the effects of psychostimulants on cognitive function in individuals with ADHD. Method: A systematic search of PubMed, Scopus, and Web of Science from inception to July 2021 was conducted. Additional studies were identified through Google Scholar and a manual search of the reference lists of relevant articles. Inclusion criteria were original studies that evaluated the cognitive function of individuals with ADHD taking psychostimulants drugs. We assessed the quality of the included papers using the Newcastle–Ottawa scale (NOS). Results: A total of 10 studies involving 753 subjects with ADHD and 194 healthy controls were identified and eligible for inclusion. Nine studies evaluated the impact of methylphenidate on cognitive function and one study investigated the use of lisdexamfetamine. Results indicated that attentional deficits such as memory, vigilance, divided attention, phasic and tonic alertness, and focused attention were improved in ADHD patients treated with psychostimulants. The efficacy of psychostimulants in improving other domains of cognition remains inconclusive due to conflicting evidence or insignificant findings (ie. academic performance and executive function). Overall, results indicate that psychostimulants may improve only select domains of cognition (ie. memory and attention). Conclusion: Psychostimulants are reported to improve several disparate aspects of cognition among individuals with ADHD. Further research is needed to better understand the complex relationships between cognition and behavior in ADHD, as well as the impact of medication on these distinct aspects of functioning. Further research is also needed to determine whether the pro-cognitive effect of stimulants would be transferable to other mental disorders.